Decarbonization of the heating sector from a system point of view: the case study of the Lombardy Region. Issue 1 (1st December 2022) - Marianna, Pozzi; Muliere, Giuseppe; Mezzera, Francesco; Fattori, Fabrizio; Dénarié, Alice; Motta, Mario; Mazzarella, Livio
Abstract: This work aims at defining the optimal technological mix which minimizes the total cost of the energy system in 2030 in the Lombardy region, in northern Italy. The goal is reached through a bottom-up model built on a linear optimization problem considering different technical and economic inputs and constraints. Civil sector is one of the sectors to focus on for the decarbonization process. Different areas, types of buildings and thermal systems are included in the model to consider the peculiarities of the available solutions in each context. The overall technological mix is constraint by a CO2 emission limit. For the civil sector the more the emission is constrained, the higher is the penetrations of electric heat pumps, coupled with envelope retrofit, (10% of the total thermal energy demand) and of district heating (18%), while natural gas boilers decrease (66%). Biomass boilers reach a maximum penetration of 29% in mountain areas. District heating is relevant in areas with available sources (max 29%). Natural gas boilers coupled with air conditioners have an important role and they reach a maximum penetration of 89% in certain areas. Electric heat pumps are quite homogeneous through the areas for residential buildings.